Discrepancy between Health Care Rationing at the Bedside and Policy Level. (October 2018) - Persson, Emil; Andersson, David; Back, Lovisa; Davidson, Thomas; Johannisson, Emma; Tinghög, Gustav
Background. Whether doctors at the bedside level should be engaged in health care rationing is a controversial topic that has spurred much debate. From an empirical point of view, a key issue is whether there exists a behavioral difference between rationing at the bedside and policy level. Psychological theory suggests that we should indeed expect such a difference, but existing empirical evidence is inconclusive.Objective. To explore whether rationing decisions taken at the bedside level are different from rationing decisions taken at the policy level.Method. Behavioral experiment where participants ( n = 573) made rationing decisions in hypothetical scenarios. Participants (medical and nonmedical students) were randomly assigned to either a bedside or a policy condition. Each scenario involved 1 decision, concerning either a life-saving medical treatment or a quality-of-life improving treatment. All scenarios were identical across the bedside and policy condition except for the level of decision making.Results. We found a discrepancy between health care rationing at policy and bedside level for scenarios involving life-saving decisions, where subjects rationed treatments to a greater extent at the policy level compared to bedside level (35.6% v. 29.3%, P = 0.001). Medical students were more likely to ration care compared to nonmedical students. Follow-up questions showed that bedside rationing was more emotionally burdensome than rationing at the policy level, indicating that psychological factors likely play a key role in explaining the observed behavioral differences. We found no difference in rationing between bedside and policy level for quality-of-life improving treatments (54.6% v. 55.7%, P = 0.507).Conclusions. Our results indicate a robust "bedside effect" in the life-saving domain of health care rationing decisions, thereby adding new insights to the understanding of the malleability of preferences related to resource allocation.